A Systematic and Comparative Review of Behavior Change Strategies in Stress Management Apps: Opportunities for Improvement - Alhasani, Mona; Mulchandani, Dinesh; Oyebode, Oladapo; Baghaei, Nilufar; Orji, Rita (Frontiers in Public Health, 2022)
Stress is one of the significant triggers of several physiological and psychological illnesses. Mobile health apps have been used to deliver various stress management interventions and coping strategies over the years. However, little work exists on persuasive strategies employed in stress management apps to promote behaviour change. To address this gap, we review 150 stress management apps on both Google Play and Apple’s App Store in three stages. First, we deconstruct and compare the persuasive/behaviour change strategies operationalized in the apps using the Persuasive Systems Design (PSD) framework and Cialdini’s Principles of Persuasion. Our results show that the most frequently employed strategies are personalization, followed by self-monitoring, and trustworthiness, while social support strategies such as competition, cooperation and social comparison are the least employed. Second, we compare our findings within the stress management domain with those from other mental health domains to uncover further insights. Finally, we reflect on our findings and offer eight design recommendations to improve the effectiveness of stress management apps and foster future research.